QUALITY WORK OF LIFE DALAM MENINGKATKAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR, DAN KINERJA KARYAWAN - Ryan Pahlawan (Universitas Lancang Kuning, 2023)
This study aims to analyze the effect of quality work on organizational citizenship behavior and employee performance. The sample for this research is government-owned credit insurance employees in Riau Province, totaling 324 people. The technique used is the census method. The data analysis technique used is SEM-PLS. The results of this study indicate that a) quality of work life has a positive and significant influence on organizational citizenship behavior; b) quality of work life has a positive and significant influence on employee performance; c) organizational citizenship behavior has a positive and significant influence on employee performance; and d) quality of work life has a positive and significant influence on employee performance through organizational citizenship behavior. Based on the results of this study, companies must pay extra attention to employees, especially in a comfortable work environment, in order to create an increase in organizational citizenship behavior and employee performance